Transactions on Petri Nets and Other Models of Concurrency VIII - Koutny, Maciej; Aalst, Wil M. P.; Yakovlev, Alex.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The 8th volume of ToPNoC contains revised and extended versions of a selection of the best workshop papers presented at the 33rd International Conference on Application and Theory of Petri Nets and Other Models of Concurrency (Petri Nets 2012). The 10 papers cover a diverse range of topics including model checking and system verification, refinement and synthesis, foundational work on specific classes of Petri nets, and innovative applications of Petri nets and other models of concurrency. Application areas covered in this volume are: biological systems, communication protocols, business processes, collaborative team work, and Petri net education. Thus this volume gives a good view of ongoing concurrent systems and Petri nets research.
Comparing Metabolic Pathways through Reactions and Potential Fluxes -- Modeling and Analyzing Wireless Sensor Networks with VeriSensor: An Integrated Workflow -- Local State Refinement and Composition of Elementary Net Systems: An Approach Based on Morphisms -- From Code to Coloured Petri Nets: Modelling Guidelines -- Using Integer Time Steps for Checking Branching Time Properties of Time Petri Nets -- When Can We Trust a Third Party?: A Soundness Perspective -- Hybrid Petri Nets for Modelling the Eukaryotic Cell Cycle -- Simulative Model Checking of Steady State and Time-Unbounded Temporal Operators -- Model-Driven Middleware Support for Team-Oriented Process Management -- Grade/CPN: A Tool and Temporal Logic for Testing Colored Petri Net Models in Teaching.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs